Do weapons facilitate adolescent delinquency?: an examination of weapon carrying and delinquency among adolescents - Emmert, Amanda D. (Crime & delinquency, 2018)
This article examines whether weapon carrying influences the frequency and variety of violent, property, and drug delinquency adolescents commit through fixed-effects analyses of data from the Rochester Youth Development Study (RYDS). We conclude that weapon carrying contributes to violent, substance, and property delinquency, and delinquent behaviors learned during weapon carrying continue to affect substance and property delinquency long after carrying has ceased.